Increasing Dependency Ratios, Pensions, and Tax Smoothing - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1998)
The implication of increasing dependency ratios for pay-as-you-go, defined-benefit pension programs are examined. Modifications aimed at smoothing contributions while maintaining benefits intact are analyzed for both open and closed economies.